Volume change in compacted claystone-bentonite mixtures as affected by the swamp acidic water - Arifin, Yulian Firmana; Arsyad, Muhammad; Monica, Jeane; Agus, Setianto Samingan (Communications in Science and Technology, 2021)
Water containing sulfuric acid with a pH up to 3 is prevalent in swampy areas. This article focuses on the effects of the solution on volume change of compacted claystone?bentonite mixture. Claystone was obtained from Banjarbakula landfill and it was mixed with bentonite on a 5, 10, 15, and 20% dry mass basis. Samples possessed the dry density of 16 kN/m3 and moisture content of 10, 15, and 20%. The odometer examined the samples' swelling and compression in both pure and acidic water. Characterization tests i.e., XRF, XRD, and FTIR were also performed. The results showed that swelling and compression were affected by initial moisture and bentonite content. Samples with a moisture content of 20% showed compression in acidic water. Acidic water changed the water absorbed on the clay surface without altering the mineral. A mixture containing 20% bentonite compacted to optimum moisture content was found at best in reducing the acidic water effects.